THEORY AND PRACTICE OF ACADEMIC STUDENT EXCHANGES AND CO-OPERATION BETWEEN CHINESE AND RUSSIAN UNIVERSITIES - Li Wenze (Russian Studies in Culture and Society)
The theory of academic exchanges emphasises the importance of international cooperation to improve the quality of education, stimulate innovation and promote cultural diversity. China and Russia are two major world powers with rich history and culture. The exchange of international students between the countries is an important aspect of the friendly format of cooperation in higher education. During such exchange, students can improve their foreign language skills, enrich their personal life experience, ensure high competitiveness in employment, and expand their knowledge and skills in the field of their profession. This paper analyses the current situation and predicts future directions of educational exchange through various prisms, including the experience of academic student exchange between universities in the two countries. It analyses the attitudes of Chinese students studying at SPbSU towards higher education in Russia. The author notes that academic exchanges and foreign learning experiences provide opportunities for international students to broaden their horizons and fulfil their emotional needs in study and life. Students from both countries have the opportunity to immerse themselves in a different cultural and academic environment, improve their intercultural communication skills and broaden their global perspectives. It also focuses on the opinion of Chinese students about the quality of higher education in Russia. Academic exchanges of students are of great importance for the state, as they act as instruments of forming «soft power» in another country, strengthen diplomatic relations between countries, form a positive image of the state, attract investments, etc. Thus, academic exchanges are a way for countries to develop cooperation at various levels - from educational to economic. Thus, academic exchanges are a way for countries to develop co-operation at various levels - from educational to economic.